Parkinson's Law and Its Implications for Project Management - Gutierrez, Genaro J.; Kouvelis, Panagiotis (Management Science, 1991)
Critical path models concerning project management (i.e. PERT/CPM) fail to account for work force behavioral effects on the expected project completion time. In this paper, we provide a modelling framework for project management activities, that ultimately accounts for expected worker behavior under Parkinson's Law. A stochastic activity completion time model is used to formally state Parkinson's Law. The developed model helps to examine the effects of information release policies on subcontractors of project activities, and to develop managerial policies for setting appropriate deadlines for series or parallel project activities.